Quantification of pulmonary disease activity in sarcoidosis measured with 18F-FDG PET/CT: SUVmax versus total lung glycolysis - Milou C. Schimmelpennink; Adriane D. M. Vorselaars; Marcel Veltkamp; Ruth G. M. Keijsers (EJNMMI Research, 2019)
Abstract Background 18F-FDG PET/CT has proven to be a reliable tool for therapy monitoring in sarcoidosis. Previous PET studies investigated the SUVmax as a marker for disease activity. Total lung glycolysis (TLuG) is a new tool, quantifying the glycolysis of the entire lung. Since SUVmax represents the maximum activity in only one pixel, we hypothesize that TLuG is a more accurate marker for active pulmonary disease and predictor of response than SUVmax. Methods In this retrospective cohort study, 27 patients started on infliximab for refractory pulmonary sarcoidosis. Patients received infliximab intravenously monthly at a dose of 5 mg/kg. We performed a lung function test and an 18F-FDG PET/CT before initiation of infliximab and after 6 months of treatment. SUVmax and TLuG were determined in the pre- and post-scan. Change in lung function was correlated with the change in SUVmax and TLuG and was correlated to the initial SUVmax and TLuG to evaluate the predictive value of the initial metabolic activity. Results ΔSUVmax significantly correlated with ΔFVC (r = − 0.497, p = 0.008) and with ΔFEV1 (r = − 0.467, p = 0.014). Furthermore, ΔTLuG significantly correlated with ΔFVC (r = − 0.430, p = 0.025), ΔFEV1 (r = − 0.532, p = 0.004) and ΔDLCOc (r = − 0.423, p = 0.039). Change in SUVmax and TLuG significantly correlated (r = 0.735, p < 0.001). Initial SUVmax significantly correlated with the change in FVC and DLCOc. In addition, initial TLuG significantly correlated with the change in FEV1 and DLCOc. A SUVmax > 7.5 at initiation of infliximab was predictive for 5% response in FVC, whereas SUVmax > 9.2 was predictive for 5% response in DLCOc. In addition, high TLuG > 4100 at initiation of infliximab was predictive for 5% response in FVC and FEV1 and TLuG > 4500 was predictive for response in DLCOc. Conclusion SUVmax and TLuG are equal in determining the response to infliximab in pulmonary sarcoidosis patients. Furthermore, SUVmax and TLuG at initiation of infliximab can predict change in lung function after treatment. Since TLuG is a more time-consuming tool, we recommend to use SUVmax of the lung parenchyma for response monitoring in pulmonary sarcoidosis.